The EU Digital Markets Act: Assessing the quality of regulation - Matthias Bauer; Fredrik Erixon; Oscar Guinea; Erik Van der Marel; Vanikaka Sharma (European Centre for International Political Economy (ECIPE), 2022)
The proposed Digital Markets Act (DMA) is an opportunity to prevent and remedy anti-competitive conduct by large digital platforms. If the Act is designed in an adequate manner to target specific problems, it can improve the contestability of platform services markets and markets that rely substantially on digital services. However, the DMA takes a novel approach to regulation, and novelty in concepts and regulatory requirements can lead to outcomes that later have to be corrected. Fortunately, the EU is not alone in experimenting with new regulations that specifically target the market power of large digital platforms. There is a great scope for policymakers to learn from similar frameworks in Europe and the United States. In this study, we compare key parts of the DMA proposal with similar legislation implemented or proposed in Germany, the United Kingdom and the United States - in light of established principles for good regulatory design. We analyse the structure and quality of these regulations, not if they go in a certain ideological, political or commercial direction. We find that there are some areas where the EU could learn from other proposals to make the DMA more fit for purpose, and avoid unintended consequences on Europe's economy.
Keywords: 330; Daten; Digitale Plattform; Online-Handel; Regulierung; IT-Recht; EU-Recht; Vergleich; Deutschland; USA